SULA: A PORTRAYAL OF BLACK AMERICAN WOMAN AS HEAD OF THE FAMILY - Ekawati Marhaenny Dukut (Soegijapranata Catholic University, 2003)
In a world of patriarchy, the head of a family is usua/ v the male. However, under certain circumstances, such as the depression era of the 1930s that the Black American family had to face, the mother is forced to become the head of the family. Through a brief look at history, actual v the function of Black American woman as the key person of upholding the family ties and sustaining thefamity 's livelihood has been carried out ever since the Blacks arrived in America as slaves. 7'hrough one kind of cultural studies approach, i. e. an American studies approach, the article discusses this event through a close analysis of the female characters described in the novel 'Sula '.